MENELITI IDEOLOGI MEDIA : CATATAN SINGKAT - Pawito Pawito (Profetik: Jurnal Komunikasi, 2014)
The article deals with media studies attempting to dismantle ideological values conveyed by the content of mass media. After tries to elaborate the significance role of providing the public with constructed reality by means of making representation, the article suggests three methods of inquiry i.e content analysis, semiotic analysis, and critical discourse analysis with some of exemplars.